PENGARUH IMPLEMENTASI RELATIONSHIP MARKETING TERHADAP LOYALITAS PELANGGAN PRODUK INDIHOME PADA PT. TELKOM INDONESIA CABANG PADANGSIDIMPUAN - Fatahuddin Aziz Siregar; Nida Amalia (Institut Agama Islam Negeri Padangsidimpuan, 2017)
The problem of this research is motivated by PT. Telkom Indonesia has implemented good relationship marketing with customers at the beginning of using Indihome products. However, many customers still do not heed the rules. This is because many customers submit network complaints that sometimes experience interference, the delay in paying bills even states the inability to pay bills after using Indihome products to finally decide not to subscribe again. The purpose of this study is to determine whether relationship marketing has a significant influence on customer loyalty of Indihome products at PT. Telkom Indonesia, Padangsidimpuan Branch. The discussion in this study relates to economics, especially business management. In connection with that, the approach taken is theories relating to customer loyalty, relationship marketing, communication, commitment and handling complaints. This research is a quantitative study using multiple linear regression analysis. The technique of collecting data using a questionnaire with a sample of 97 customers with the sampling technique is Random Sampling. Data processing is done with SPSS version 22. The results of this study show partially that communication has no effect on customer loyalty with tcount ttable (1.511 1.661), commitment has an influence on customer loyalty with tcount ttable (4.230 1.661), complaint handling has an influence on customer loyalty with value t count t table (2.525 1.661. Based on the simultaneous test results that communication, commitment, complaint handling have an influence on customer loyalty with Fcount Ftable (37,477 2,14). Based on the test results the coefficient of determination can be seen that 54.7% variable communication, commitment, complaint handling affect customer loyalty and the remaining 45.3% is influenced by other variables not discussed in this study. Keywords: Relationship Marketing, Customer, Loyalty